2019
DOI: 10.1108/jea-08-2018-0153
|View full text |Cite
|
Sign up to set email alerts
|

Differences in state- and district-level stakeholders’ perceptions of curriculum coherence and school impact in national curriculum reform

Abstract: Purpose Shared understandings of curriculum reform within and between the levels of the educational system are suggested to be crucial for the reform to take root. The purpose of this paper is to explore variation in perceived curriculum coherence and school impact among state- and district-level stakeholders. Design/methodology/approach The participants (n=666) included state- and district-level stakeholders involved in a national curriculum reform in Finland. Latent profile analysis was employed to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…According to our recent research findings, curriculum coherence perceived by district-level stakeholders involved in the development of local curricula contributes to their perceptions of the reform's impact on school-level development work, in terms of committing teachers to the development work and supporting development of locally functional solutions (Sullanmaa et al, 2019a). We also found that district-level stakeholders responsible for the construction of local curricula were more likely to perceive the consistency of the intended direction of the core curriculum and the school impact of the reform lower than state-level stakeholders responsible for constructing the core curriculum (Sullanmaa et al, 2019b). Thus, teachers' perceptions of curriculum coherence may also vary depending on how the curriculum development process has been organized and supported on the district and school levels, and on how individual educational practitioners have constructed shared and coherent understandings of the change.…”
Section: Curriculum Coherencementioning
confidence: 66%
“…According to our recent research findings, curriculum coherence perceived by district-level stakeholders involved in the development of local curricula contributes to their perceptions of the reform's impact on school-level development work, in terms of committing teachers to the development work and supporting development of locally functional solutions (Sullanmaa et al, 2019a). We also found that district-level stakeholders responsible for the construction of local curricula were more likely to perceive the consistency of the intended direction of the core curriculum and the school impact of the reform lower than state-level stakeholders responsible for constructing the core curriculum (Sullanmaa et al, 2019b). Thus, teachers' perceptions of curriculum coherence may also vary depending on how the curriculum development process has been organized and supported on the district and school levels, and on how individual educational practitioners have constructed shared and coherent understandings of the change.…”
Section: Curriculum Coherencementioning
confidence: 66%
“…This qualitative study aims to describe a "lived experience" of a phenomenon, focusing on the experiences and beliefs of principals and policy makers during the implementation of a national reform. This method is similar to previous work that has been done in the educational field (Colestock & Sherin, 2009;Sullanmaa et al, 2019).…”
Section: Methodsmentioning
confidence: 76%
“…Coherence between the primary stakeholders involved in educational reform is a key determinant of its success (Sullanmaa et al, 2019). Coherence refers to the individual and collective ability to build a shared depth of meaning, capacity and commitment to action (Fullan & Quinn, 2015).…”
Section: Crafting Coherence While Implementing a Pedagogical Generall...mentioning
confidence: 99%
See 2 more Smart Citations